Interactions Between Opioids and Dextroamphetamine on Locomotor Activity: Influence of an Opioid's Relative Efficacy at the Mu Receptor - Smith, Mark A.; Ballard, Shannon L.; Ballesteros, Clarise F.; Bonge, Samantha A.; Casimir, Alexander T.; Childs, Lauren M.; Feinstein, Max A.; Griffith, Annie K.; Johansen, Alexandra N.; Lee, Daegeon; Mauser, A. Caroline; Moses, Cassidy M.; et al. (Frontiers in Psychiatry, 2022)
Opioids and stimulants are often used in combination for both recreational and nonrecreational purposes. High-efficacy mu opioid agonists generally increase the behavioral effects of stimulants, whereas opioid receptor antagonists generally attenuate the behavioral effects of stimulants; however, less is known regarding the interactions between stimulants and opioids possessing low to intermediate efficacy at the mu receptor. The purpose of this study was to examine the role of an opioid’s relative efficacy at the mu receptor in altering the behavioral effects of dextro(d-)amphetamine. To this end, opioids possessing a range of relative efficacy at the mu receptor were examined alone and in combination with cumulative doses of d-amphetamine on a test of open-field, locomotor activity in male rats. Levorphanol, buprenorphine, butorphanol, nalbuphine, (-)-pentazocine, (-)-metazocine, (-)-cyclazocine, (-)-NANM, and nalorphine increased the locomotor effects of d-amphetamine in either an additive or greater-than-additive manner according to an effect-additive model. Only the selective, high-efficacy kappa agonist, spiradoline, and the nonselective opioid receptor antagonist, naloxone, failed to increase the effects of d-amphetamine under the conditions examined. These data indicate that opioids possessing a large range of relative efficacy at the mu receptor, including those possessing very low relative efficacy, significantly increase the locomotor effects of d-amphetamine.